Penny for Your Thoughts? The Protective Effect of Youths’ Attitudes Against Drug Use in High-Risk Communities - Fagan, Abigail A. (2014)
Individual-level attitudes about drugs are strong predictors of substance use among adolescents, and aggregate-level community norms regarding deviancy and drug use may influence youth attitudes as well as their drug use. This study examined the direct effects of neighborhood norms about deviance, disadvantage, immigrant concentration, and residential stability on youths’ attitudes about drug harmfulness as well as their variety of past month substance use. The moderating effect of community norms on the relationship between youth attitudes and drug use was also examined. Results suggest that community norms favorable to deviance and drug use reduced youth’s attitudes that drugs were harmful. Further, youth’s perceptions of drug harmfulness significantly reduced their substance use in the past month. Neighborhood concentrated immigration also significantly reduced substance use. Finally, living in areas where norms were favorable to deviance enhanced the protective effect of youths’ perceptions. Implications for research and substance use prevention strategies are discussed